Levels of follicular G-CSF and interleukin-15 appear as noninvasive biomarkers of subsequent successful birth in modified natural in vitro fertilization/intracytoplasmic sperm injection cycles - Lédée, Nathalie; Frydman, René; Osipova, Agnessia; Taieb, Joelle; Gallot, Vanessa; Lombardelli, Letizia; Logiodice, Federica; Petitbarat, Marie; Fanchin, Renato; Chaouat, Gérard; Achour-Frydman, Nelly; Piccinni, Marie Pierre (Fertility and sterility, 2011)
To explore oocyte competence for subsequent birth. The modified natural IVF/intracytoplasmic sperm injection (ICSI) cycle was used as an experimental model by measuring levels of cytokines, chemokines, and growth factors in individual follicular fluids (FF). A retrospective blinded study. European network of research, Embryo Implantation Control (EMBIC). Single FF from 83 women were analyzed during a modified natural IVF/ICSI cycle, and reproducibility of follicular composition was evaluated over two cycles for 15 patients. Each FF sample was blindly tested to assess levels of 26 factors by bead-based immunoassays. Each mediator was evaluated as a potential biomarker of subsequent birth by multivariate regression analysis. A combination of both FF G-CSF and IL-15 was the optimal model to predict birth (AUC ROC, 0.85). Birth rates per cycle were 48.9% (16/33) if two good-prognosis criteria were present (FF G-CSF >12 pg/mL and IL-15 <7 pg/mL) and 8% (3/36) and 0% (0/14) if, respectively, one or none were present. FF G-CSF was significantly correlated over two cycles ( r = .71), suggesting a possible prognostic value of its documentation. Combined follicular G-CSF and IL-15 quantification appears as an efficient and noninvasive method to define oocyte competence for subsequent successful conception in modified natural IVF/ICSI cycles.